BLOCKCHAIN AS A TOOL FOR TRANSPARENCY AND PROTECTION OF GOVERNMENT REGISTRIES - Balatska, Valeriia; Opirskyy, Ivan (Ukrainian Scientific Journal of Information Security, 2024)
With the advancement of digital technologies and the growing demand for transparency and data security, government registration systems face several challenges associated with their centralized architecture. Traditional centralized systems used for storing and processing data exhibit various problems, including vulnerability to cyberattacks, insufficient protection of personal data, lack of user control over their information, and non-compliance with international standards, such as the General Data Protection Regulation (GDPR). This creates the need for the adoption of new technological solutions capable of addressing these shortcomings and ensuring enhanced reliability for government registries. This research proposes the implementation of blockchain technologies in government registration systems as a solution capable of improving data security, transparency, and reliability while providing users with greater control over their personal information. Blockchain enables the creation of decentralized systems where data cannot be altered without proper authentication, and all transactions are recorded, reducing the risk of unauthorized access and fraud. A key element of this study is the development of a mathematical model for quantitatively assessing the effectiveness of blockchain adoption in government registration systems. The model evaluates security, transparency, reliability, and data processing speed indicators, allowing for a comparison with traditional centralized systems. The analysis shows that blockchain can significantly reduce corruption risks, ensure full transparency of government processes, and improve citizens' trust in public institutions. Moreover, blockchain implementation complies with international data security and protection standards, such as GDPR, making this technology a promising tool for public administration. The study also highlights key directions for blockchain development, including improving system scalability, optimizing data processing costs, and integrating with other technologies for public governance. The findings demonstrate the significant potential of blockchain solutions to transform government registries, and the developed model can be used as a tool for further research and implementation of the technology in public institutions.